Pengembangan Model Pembelajaran Flipped Classroom Berbasis Board Game untuk Meningkatkan Ekologi Kewargaan (Civic Ecology) - Elisa Seftriyana; Resti Apriliyana (Universitas Muhammadiyah Ponorogo, 2026)
This study aimed to develop a board game-based flipped classroom learning model to enhance civic ecology among junior high school students in Bandar Lampung City. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The developed product included the Eco Quest board game, pre-class learning videos, lesson plans, student worksheets, and civic ecology assessment instruments. The product was validated by three experts (instructional design, Civic Education, and educational media) and achieved an overall Content Validity Ratio (CVR) of 0.82, indicating validity. The implementation stage applied a quasi-experimental pretest-posttest control group design involving 300 students (150 experimental; 150 control) from five public junior high schools in Bandar Lampung City. Civic ecology was measured using the validated Civic Ecology Scale (CES) (Cronbach’s alpha = 0.87), covering civic knowledge, civic attitudes, and civic actions. Results showed that the experimental group achieved a higher mean post-test score (85.98) than the control group (73.24) (t = 18.743; df = 298; p = 0.000). N-Gain analysis indicated moderate improvement in the experimental group (g = 0.623) and low improvement in the control group (g = 0.286), with consistent results across all schools (SD of gain difference = 0.579). These findings demonstrate that the board game-based flipped classroom model effectively bridges the gap between civic knowledge and civic action, fostering ecologically responsible citizens oriented toward justice and grounded in Pancasila values.